Yto Barrada : figures de résistance à la domestication de l’espace - Évelyne Toussaint (Itinéraires)
The landscape is often the ground of politics, marked by power, hegemony and daily resistance to them. Yto Barrada bases her artistic approach on the observation of what she calls “resistance to the domestication of space.” With a keen eye and a claimed tenderness, she describes not only the “property emergency” and “auto-folklorization” of the city of Tangier, but also its interstices of freedom.